ANALISIS PENGARUH ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Manufaktur di BEI Tahun 2017-2019) - Angelica, Felicia; ., Mohklas; Latifah, Nurul (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to analyze the effect of stock returns. The independent variables include Economic Value Added (EVA) and Market Value Added (MVA). This study uses secondary data derived from the annual financial statements. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 – 2019. The sampling technique used was purposive sampling and the number of samples was 57 data. The data analysis method used multiple linear regression. The results of this study indicate that the Economic Value Added (EVA) has an effect and is significant on stock returns. Market Value Added (MVA) has no significant effect on stock returns.Keywords: Economic Value Added (EVA), Market Value Added (MVA), stock returns.